Prevalence and associated factors of reading spectacle coverage among adults aged 35 years and above living in Debre Berhan Town, North Shewa, Ethiopia, 2023 - Bekele, Matiyas Mamo; Tegegn, Melkamu Temeselew; Adimassu, Nebiyat Feleke; Sinshaw Assem, Abel; CheklieZeleke, Tarekegn; Zigale Bayabil, Abebizuhan; Birhan, Getenet Shumet; Shumye, Abebech Fikade (Frontiers in Ophthalmology, 2025)
IntroductionNear vision impairment can be addressed through several methods, including spectacles, contact lenses, miotic drugs, and refractive surgery. Of these options, spectacles are the most commonly used, affordable, and accessible solution. Reading spectacle coverage is an important indicator of admittance and eye care service utilization. Additionally, it serves as a valuable tool for monitoring progress toward achieving universal eye health coverage worldwide.ObjectiveThe aim of this study was to assess the prevalence and associated factors of reading spectacle coverage among adults aged 35 years and above living in Debre Berhan town, North Shewa, Ethiopia.MethodsA community-based cross-sectional study involving 808 adults was conducted in Debre Berhan town from May 8 to June 8, 2023, utilizing a multistage sampling technique. Data were gathered using a pre-tested, structured questionnaire administered by interviewers. The information was collected through Kobo Collect version 2021.4.4 and subsequently exported to Stata version 14 for processing and analysis. A binary logistic regression analysis was performed to identify the factors associated with reading spectacle coverage. Variables with a p-value of less than 0.05 in the multivariable binary logistic regression were deemed statistically significant.ResultsA total of 780 participants took part in the study, resulting in a response rate of 96.53%. The average age of the participants was 49.58 ± 9.31 years. The proportion of reading spectacle coverage was 32.69% (95% CI: 28.82, 36.31). Factors positively associated with reading spectacle coverage included higher educational status (AOR = 3.10, 95% CI: 1.59, 6.05), awareness of near vision problems (AOR = 3.24, 95% CI: 2.08, 5.05), a history of eye examination (AOR = 3.16, 95% CI: 1.58, 6.55), experiencing difficulties with near vision (AOR = 2.56, 95% CI: 1.26, 5.21), and adding plus lens power used ≥2.50D (AOR = 1.26, 95% CI: 1.13, 3.16).ConclusionThe study found that the proportion of reading spectacle coverage was low. A higher level of education, history of awareness of near vision problems, history of difficulties in near vision, history of eye examination, and high adding lens power used were significantly associated with reading spectacle coverage.